How to Adjust to a Large Fall in Commodity Prices - Medas, Paulo; Danforth, Jeff.; Salins, Veronique (Washington, D.C. : International Monetary Fund, 2016)
Resource-rich countries have to manage highly volatile commodity revenues. In periods of revenue booms there is a tendency for large spending scale-ups. When facing large and persistent reductions in commodity prices, some of these countries will need to adjust their budgets to the new reality. In many cases, overall surpluses turn into large fiscal deficits and borrowing costs tend to rise with the fall in commodity prices. This note discusses how to undertake large fiscal adjustments, which often tend to be protracted and with long-lasting impacts on growth. Consequently, the note also highlights how to better prepare for future booms and busts in commodity prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet